2016
DOI: 10.1093/ee/nvw160
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature and Host Plant Resistance on Population Growth of the Soybean Aphid Biotype 1 (Hemiptera: Aphididae)

Abstract: A laboratory experiment was conducted to evaluate direct and indirect effects of temperature on demographic traits and population growth of biotype 1 of the soybean aphid, Aphis glycines Matsumura. Our objectives were to better understand how temperature influences the expression of host plant resistance, quantify the individual and interactive effects of plant resistance and temperature on soybean aphid population growth, and generate thermal constants for predicting temperature-dependent development on both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Research with the soybean aphid provides equivocal evidence that plant resistance increases at both higher and lower temperatures compared to a middle range of noninducing temperatures. Hough et al (2017) recorded a lower rate of survival of the soybean aphid on resistant plants compared to susceptible plants at all temperatures (range 15-30°C). However, whereas survival on the resistant soybean line decreased sharply between 25 and 30°C, survival was equally high at the same two temperatures on the susceptible line.…”
Section: Enhanced Resistance At High and Low Temperaturesmentioning
confidence: 90%
See 4 more Smart Citations
“…Research with the soybean aphid provides equivocal evidence that plant resistance increases at both higher and lower temperatures compared to a middle range of noninducing temperatures. Hough et al (2017) recorded a lower rate of survival of the soybean aphid on resistant plants compared to susceptible plants at all temperatures (range 15-30°C). However, whereas survival on the resistant soybean line decreased sharply between 25 and 30°C, survival was equally high at the same two temperatures on the susceptible line.…”
Section: Enhanced Resistance At High and Low Temperaturesmentioning
confidence: 90%
“…In the soybean aphid, Aphis glycines Matsumura (Hemiptera: Aphididae), Hough et al (2017) reported consistently lower survival on a resistant soybean (Glycine max (L.) Merrill [Fabales: Fabaceae]) line compared to a susceptible line at temperatures that ranged from 15 to 30°C. However, whereas aphid survival was equally high at 25 and 30°C on susceptible soybeans, on resistant plants there was a sharp decrease in survival between 25 and 30°C.…”
Section: Enhanced Resistance At High Temperaturesmentioning
confidence: 99%
See 3 more Smart Citations